A Decentralized Health Data Repository for Remote Patient Monitoring Using Blockchain and FHIR - Vieira, Marcos Alves; Velasco, Gislainy Crisostomo; Carvalho, Sergio T. (Workshop em Blockchain: Teoria, Tecnologias e Aplicações (WBlockchain), 2023)
The world’s aging population increasingly faces challenges in accessing healthcare due to a shortage of healthcare professionals. Telemedicine and remote patient monitoring solutions offer a promising avenue for improving access to care, allowing for the monitoring of physiological data, activities performed, and the conditions of the patient’s environment. However, such systems must address numerous challenges, such as interoperability, security, integrity, and confidentiality of medical data. In this paper, we propose a repository architecture for medical data obtained through remote patient monitoring. Our solution relies on the Fast Healthcare Interoperability Resources (FHIR) standard to address interoperability issues, while the inherent characteristics of blockchain technology provide security, integrity, and confidentiality of stored data. In addition to remote patient monitoring, the proposed repository has the potential to be used for scientific research, data mining and analysis applications among other health applications. Ongoing implementation and testing of the repository in a real-world setting will demonstrate its performance and scalability. Meanwhile, we present the architecture and constituent elements, including data flow and smart contracts, with their responsibilities described. Overall, our proposed solution offers a promising approach to addressing the challenges of remote patient monitoring and storing medical data securely and efficiently.